ANALISIS STRATEGI PENDISTRIBUSIAN HARGA GLOBAL DALAM PEMASARAN INTERNASIONAL - Samosir, Wiranto; Damanik, Andex Yosepril; Br. Munthe, Gresia Mayasari; Bestari, Dinda; Saragih, Lenti Susanna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to comprehensively analyze the basic concepts, mechanisms, barriers, and strategic impacts of global price distribution within the architecture of international marketing. Along with economic integration, international distribution networks face critical phenomena such as price escalation, gray markets, and channel conflicts that can potentially degrade foreign brand value and diminish global consumer satisfaction. Using a qualitative approach based on library research and content analysis methods, this paper reviews secondary data from reputable academic literature. The findings demonstrate that pricing strategies in the global arena cannot be detached from international supply chains. Factors such as corporate tax disparities, transfer pricing dynamics, institutional distance, and high logistics costs act as primary drivers of price escalation. Contemporarily, the emergence of digital ecosystems and e-commerce global platforms enables international firms to leverage personalized dynamic pricing and bypass traditional geographical intermediaries. The study concludes that successful global price distribution relies on a triadic convergence of efficient digital supply chains, aggressive promotion, and competitive value-based pricing to maintain purchasing power and drive long-term export performance. Keywords: Global Pricing, Price Distribution, International Marketing, Price Escalation